2012
DOI: 10.1371/journal.pone.0046520
|View full text |Cite|
|
Sign up to set email alerts
|

Several Different Lactase Persistence Associated Alleles and High Diversity of the Lactase Gene in the Admixed Brazilian Population

Abstract: Adult-type hypolactasia is a common phenotype caused by the lactase enzyme deficiency. The −13910 C>T polymorphism, located 14 Kb upstream of the lactase gene (LCT) in the MCM6 gene was associated with lactase persistence (LP) in Europeans. This polymorphism is rare in Africa but several other variants associated with lactase persistence were observed in Africans. The aims of this study were to identify polymorphisms in the MCM6 region associated with the lactase persistence phenotype and to determine the dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 50 publications
5
32
0
1
Order By: Relevance
“…These data indicate that in this diverse U.S. population genetic testing alone would mis-classify a large number of screened subjects when using intestinal lactase enzyme levels as a gold standard (5, 6). A similar observation was recently made in a Brazilian population (16). …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These data indicate that in this diverse U.S. population genetic testing alone would mis-classify a large number of screened subjects when using intestinal lactase enzyme levels as a gold standard (5, 6). A similar observation was recently made in a Brazilian population (16). …”
Section: Discussionsupporting
confidence: 87%
“…We did not identify any of the potential lactase persistence alleles reported to be present in European-ancestry individuals in recent publications (11-13). SNPs associated with lactase persistence in other heterogeneous populations were also absent (16-19). However, we discovered a novel C>A variant at -13909, present in both of the individuals who share a long, novel haplotype in this region (64 and 71).…”
Section: Resultsmentioning
confidence: 97%
“…This association was corroborated by several functional studies 4 , 6–9 which revealed the causal effect of rs4988235 on LP. Further genetic variability in this region has been described in non-Europeans, including admixed populations such as Brazil 10 . The gastrointestinal symptoms in response to lactose that occur (at varying levels) in individuals with adult-type hypolactasia motivated investigation of the positive association between LP and intake of milk and other dairy products 2 , 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The method of genomic control employed in this study has been used successfully in other publications by this research group. 24,[29][30][31][32][33] The results from the multivariate statistical model used to determine the association between the CYP3A5 gene A6986G polymorphism and the drugs examined did not differ between the patients with and without hepatotoxicity (p = 0.176; OR 0.562, 95% CI 0.255-1.238). The CYP3A5 gene polymorphism results are consistent with data published previously for other populations, because no association was observed between the A6986G polymorphism and drug-induced hepatotoxicity.…”
Section: Discussionmentioning
confidence: 95%